Nuances of microalgal technology in food and nutraceuticals: a review. Issue 5 (18th March 2019) - Sahni, Prashant; Aggarwal, Poonam; Sharma, Savita; Singh, Baljit
Abstract : Purpose: The purpose of this paper is to acquaint the readers with the insights regarding the interventions of microalgal technology for production of metabolites and functional ingredients from microalgae for food and nutraceutical application and exploration of microalgae biomass for food application. Design/methodology/approach: Various information databases such as journals, library catalogues and professional websites were used to collect information pertaining to application of microalgae in food and nutraceutical sector. Systematic review was made with recent studies covering the vital aspects of art of microalgae cultivation for metabolite production, functional ingredients from microalgae, market scenario and utilisation of microalgae biomass for the valorisation of the food products. Key points have been discussed after every section to highlight the practical implications to make this review more insightful for the readers. Findings: Microalgal technology provides sustainable solution for its application in food and nutraceutical sector. The heart of metabolite production lies in the optimisation of cultivation conditions of microalgae. Wide array of functional components are obtained from microalgae. Microalgae offer an alternative source for omega-3 fatty acids. Microalgae is widely exploited for production of pigments, namely, ß-carotene, astaxanthin, lutein, phycocyanin and chlorophyll, that have important implication as natural colourants and nutraceuticals in food. Larger diversity of sterols found in microalgae confers bioactivity. Microalgae is finding its place in market shelves as nutraceuticals where its functional ingredients are in the form of powder, tablets, extract and beverages and in innovative products such as microalgae protein and fat, culinary algae oil and butter. Sprulina and Chlorella are popular choice for the supplementation of food products with microalgae biomass. Originality/value: This is a comprehensive review that highlights the application of microalgal technology for the development of healthy food products and presents holistic intervention in food and nutraceutical sector.